Uneducated and less trustworthy. Social distance in subconscious language attitudes towards Lithuanian-Russian accent speakers - Žuklys-Rogoża, Prieglius (Taikomoji kalbotyra, 2024)
Sociological surveys have shown that social distance towards Lithuanian-Russians (the so-called “ethnic Russian minority” in Lithuania) is rather marginal or non-existent. This paper presents a pilot study at Vilnius schools (n=151), which used the verbal guise technique to investigate subconscious language attitudes towards Lithuanian (i) with Vilnius speech traits, (ii) with a Lithuanian-Russian accent, and (iii) with a Scandinavian accent – an accent presumed unfamiliar to the study participants. Half of the participants were also informed of the speaker’s profession to assess if it can reverse their attitudes. The main findings of the study show that speakers with a Lithuanian-Russian accent are perceived as less interesting, less educated, less trustworthy, and older. These results put into question the notion of absent social distance towards Lithuanian-Russians, highlighting the need for further research on this topic.
Keywords: subconscious language attitudes; Lithuanian-Russians (“ethnic Russian minority”); social distance; Lithuanian language with an accent; unfamiliar accent